The Effects of Advertisements on Influencing Decisions to Invest in Riskier Financial Assets - Honadi, Winston; Johan, Jeremy Christo (Journal of Business, Management, and Social Studies, 2023)
This research’s main purpose is to discover whether psychological and social factors have a significant effect on a person’s attitudes toward advertisement, ultimately affecting their investment decisions. This research utilized GOTO Stockbit’s advertisement and was distributed to the public Indonesian population who has an interest in investment. The research collected a total of 115 samples which were then filtered to only include those who had experience investing to test the possibility of investing in a riskier financial asset. The research results show that psychological factors had no significant effects on attitudes toward advertisements. However, social factor has a significant enough effect on attitudes toward advertisement, as do attitudes toward advertisement toward investment decision. The study results that social factors lead to a positive attitude toward advertisements from securities that motivate individuals to make an investment decision. However, this study’s results show that psychological factors do not lead to any investment decisions by individuals as it has little to no effect on their attitude toward advertisements. This research aims to measure the effectivity of security advertisements on the investment decisions of individuals by adding a new study goal by introducing new hypotheses involving psychological and social factors to add clarity to previous research covering investment decisions. This research hopes that security brokerage can make an effective and optimal advertisement suggested in the research.